Pengaruh Karakteristik Perusahaan dan Komite Audit Terhadap Audit Report Lag - Reny; Tanujaya, Kennardi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The effect of company characteristics and audit committee toward audit report lag is the purpose of this study. Period difference between company close book date and audit report publish date is measurement for this dependent variable. Company characteristics are measured by company size, income and leverage. The audit committee is measured by audit committee expertise, audit committee tenure, audit committee overlap, audit committee independence, audit committee size and audit committee meetings. The research object used is the companies listed on the IDX as of 2016 to 2020 with the company's annual report as a source of research data. Purposive sampling method in data collection is applied. The total data sampled were 520 companies with 1,564 data studied. The results of this study found that company size, audit opinion, income and tenure of the audit committee had a significant positive effect on audit report lag. Meanwhile, the variables of KAP size, leverage, audit committee expertise, audit committee overlap, audit committee independence, audit committee size and audit committee meeting have no significant effect on audit report lag.